The effect of the problem-based learning model by using LKPD based on south sumatera's local superiority to learn outcomes - Rizki Fitrianti; Nur Ahyani; Dessy Wardiah (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aimed to define the problem-based learning model of problem-based learning using LKPD based on South Sumatra's local benefits for students at SDN 16 Prabumulih learning outcomes. This study used Quasi Experimental Design as the Nonequivalent Control Group Design method of design. The mean pretest score in the experimental group was 82,6 and the mean pretest control score in the experimental group was 67,3. In the experimental population, pretest and posttest data were usually distributed with a value of km -0.71 and 0.80 respectively. The hypotheses were calculated using ttest, which is polled variants, and the result of t obtained was 8,598 at 0,05 relevant level and table 1,987. Therefore, Ho was rejected and Ha was approved because the substantial level showed tobtain> table. The results of this study showed that the impact model of problem-based learning using LKPD based on the local benefits of South Sumatra had a substantial impact on the learning outcomes of studies at SDN 16 Prabumulih.